Detection of Human Herpesvirus Type-1 Antigen in Tissues of Oral Squamous Cell Carcinoma by Direct Immunofluorecent Assay - Mohammed, Najwa Ahmed; Hussein, Areej Atiyah; Majeed, Ahlam Hameed (Diyala Journal of Medicine, 2019)
Background: Human herpesvirus is a large enveloped DNA virus and significant human pathogen. Many studies examined oral squamous cell carcinoma for herpes simplex virus and suggested an association with this virus; others have demonstrated human herpesvirus -1 DNA in different part of oral squamous cell carcinoma. Objective: To detect the human herpes virus -1 antigen in tissues of oral squamous cell carcinoma. Patients and methods: Fourty two formalin-fixed, paraffin embedded oral tissues blocks were collected from 30 patients with oral squamous cell and 12 individuals with apparently-healthy oral tissues from archives of histopathology laboratory of college of Dentistry -Baghdad University, during the period from 2010 till 2012. All samples were related to the period between 2004 to 2009. Human herpesvirus -1 antigen was detected by direct immunofluorecent assay (US biological, Cat. No. H2033-08E). Results: Among oral squamous cell carcinoma group, 26 formalin-fixed, paraffin embedded oral tissues blocks were found to contain HHV-1 antigen, this result constituted 86.7% of the total oral squamous cell carcinoma screened for HHV-1 antigen and 75% within apparently-healthy oral tissues. The age of patients ranged from (25-70) years with mean of 53.26 ±12.1years. The highest percentage 60% was diagnosed in the age above 50 years. The percentage in males (61.68%) was more than in females (38.31%). On the other hand there was no significant difference between viral infection, age and gender distribution, while significant correlation noticed with tumor differentiation. Conclusion: The detection of human herpesvirus -1 antigen in oral squamous cell carcinoma and apparently healthy control indicates virus with other factor such as chemicals and radiation, which play important role in the development of oral cancers